MetaTGA: a chance for BIM in the field of MEP. Issue 6 (4th December 2020) - Hauer, Stefan; Murschetz, Julian; Bres, Aurelien; Sporr, Andreas; Schöny, Michael; Monsberger, Michael
Abstract: The use of Building Information Modeling (BIM) is becoming more and more state‐of‐the‐art in the construction and real estate industries. Mechanical, electrical, and plumbing (MEP) has a major part in this field. The quality of MEP in the planning and the construction phase of a building is crucial for energy consumption and human comfort within the building. To benefit from the advantages of the BIM methodology, a high‐quality data model is needed to ensure the availability of necessary information of a complete life cycle of a building. The Austrian research project metaTGA provides solutions for high‐quality data models. The paper will provide information about: how do MEP openBIM data models need to look like? What are the major development steps of these models? How are they applied in a BIM project including first practical feedback? How does the process support quality measures for BIM projects? Abstract: Das Forschungsprojekt metaTGA: eine Chance für BIM im Bereich der Technischen Gebäudeausrüstung Der Einsatz von Building Information Modeling (BIM) wird in der Bau‐ und Immobilienbranche immer mehr zum State‐of‐the‐Art. Heizung, Klimatechnik, Lüftung und Sanitär (HKLS), vor allem die Qualität der Planung, spielen dabei eine immer größere Rolle, sowohl für den Energieverbrauch als auch für den Komfort eines Gebäudes. Um dabei die Vorteile von BIM nutzen zu können, ist ein qualitativ hochwertiges Datenmodell erforderlich um sicherzustellen, dass alle notwendigen Informationen eines Gebäudes über den gesamten Lebenszyklus für die weitere Verwendung zur Verfügung stehen. Dahingehend bietet das österreichische Forschungsprojekt metaTGA Lösungen für hochqualitative Datenmodelle an und untersucht im vorliegenden Aufsatz folgende Themen bzw. Fragestellungen: Wie müssen leistungsstarke openBIM‐Modelle aussehen? Wie schauen die wichtigsten Entwicklungsschritte der Modellierung aus? Wie wird erstes Feedback aus BIM Demo‐Projekten berücksichtigt? Wie unterstützt metaTGA hinsichtlich Qualitätssteigerung in BIM Projekten?